Analisis Problematika Guru PAI dalam Penerapan Kurikulum Merdeka di SMP Negeri 1 Padang Panjang - Putri, Amelisa; Alfurqan, Alfurqan (Asian Journal of Islamic Studies and Da'wah, 2025)
This study discusses the challenges faced by Islamic Religious Education (Pendidikan Agama Islam or PAI) teachers in implementing the Kurikulum Merdeka at SMP Negeri 1 Padang Panjang. The purpose of this research is to identify and analyze the various obstacles encountered by PAI teachers in the implementation of learning based on the Kurikulum Merdeka. A qualitative approach was used with a case study method, and data collection techniques included observation, interviews, and documentation. The findings indicate that PAI teachers face several challenges, including difficulties in applying differentiated instruction, limitations in conducting kokurikuler (P5) learning activities, and challenges in aligning learning outcomes (capaian pembelajaran or CP) with students’ needs and subject characteristics. These obstacles result in less-than-optimal implementation of the Kurikulum Merdeka in the context of PAI instruction. This study provides a concrete picture of the challenges teachers face during the curriculum transition and highlights the need for policy support, training, and strengthening of teacher competencies to enable effective and contextual implementation of the Kurikulum Merdeka.